Haikyu!!. Volume 30, Broken heart - Furudate, Haruichi, 1983- (Shonen Jump manga., 2019)
Ever since he saw the legendary player known as "the Little Giant" compete at the national volleyball finals, Shoyo Hinata has been aiming to be the best to play volleyball when you can jump higher than anyone else? The Inarizaki vs. Karasuno game continues! With their own Freak Quick and on-the-fly plays, the Miya twins and Inarizaki make it clear that they are in, in fact, the greatest contenders in the tournament. Meanwhile, Nekoma struggles through their own game against Sarukawa Tech. Will Nekoma and Karasuno make it through their games and keep the dream of the dumpster battle alive?